Revisiting peak oil theory : role of demand and technology - Bai, Jie Ying (2014)
Many studies have tried to validate Hubbert’s peak oil theory, some of which supporting it and otherwise. This study supports the argument that the theory is valid to a certain extent; however, it holds assumptions that are not true in today’s world. This study aims to revisit the peak oil theory incorporating the role of demand and technological progress. A simple mathematical model is constructed with constant demand, with three extended versions incorporating demand and technological progress. The model presents how long supply can last and the movement of the peak.